Bilirubin: jekyll and hyde pigment of life : pursuit of its structure through two world wars to the new millenium - Lightner, David A. (Progress in the Chemistry of Organic Natural Products,, 2013)
The book covers the totality of bilirubin (and heme, from which bilirubin is derived biogenetically), the structural relationship of bilirubin to its solution properties and metabolism, and to phototherapy for the jaundiced newborn - a common medical procedure used nowadays for lowering serum bilirubin, which is neurotoxic.